Arahan Penataan Lingkungan Pemukiman Kumuh Kelurahan Seberang Palinggam Kecamatan Padang Selatan Kota Padang - Elviyanti Elviyanti; Desy Aryanti; Sri Andika (Universitas Riau, 2020)
Community settlements in a city have a very important role in providing services in the field of life. Increasing the population in a strategic land in urban areas will cause urban problems, especially population density, building irregularities and slums. This increase in population is due to economic, legal, social and cultural aspects, all centered in the city so that many rural communities flock to the city to improve their economy. Seberang Palinggam Sub-District, South Padang District, Padang City is one of a strategic location because it is close to the port, trade and service area. This strategic location caused many people who settled there. As a result, Seberang Palinggam Village is included in 23 slum areas in Padang City, based on Padang Mayor Decree No. 163 of 2014. This study aims to determine the right direction in the structuring of the slum environment with the Eco-Settlement approach that develops from the concept of sustainable development. The target being developed is to identify the characteristics of slums in villages across Palinggam using the Qualitative Descriptive Method, Analysis of the factors that led to the development of slums using Delphi. From this analysis, it is obtained an outline based on influential factors in the form of adding and improving the quality of sanitation infrastructure, clean water, drainage and healthy houses, increasing the carrying capacity of the environment and community resources, empowering the community's economy, and improving the quality of institutions and awareness of existing policies related to slum environment management.